Interactional justice model, power distance, and leader-member exchange as a high quality workplace - Elly Yuliandari; Gugus Wijonarko (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
The reciprocal relationship between superiors and subordinates (leader-member exchange or LMX) influences work productivity, organizational citizenship. This study examines the relationship model of interactional justice and power distance reduction in the leader-member exchange. The study was conducted on 240 staff who have more than two years of work experience. The analysis results showed that the relationship model of Interactional Justice and Power Distance on the Leader-Member Exchange showed significant results (F =, p <0.01).